Magnetization AC losses in multilayer superconducting round cables with coinciding and opposite lay angles. (1st March 2023) - Solovyov, M; Šouc, J; Kujovič, T; Frolek, L; Gömöry, F
Abstract: Superconducting cables with a circular cross-section are attractive for various applications, such as power transmission lines, current leads, and large magnetic coils. In the case of coated conductor (CC) tapes, such an arrangement can be achieved by wrapping the tapes in a helical fashion around a circular former. While a braid of Cu wires serves as the core for the CORC ® cable, in the conductor-on-round-tube the CC tapes are laid in several layers on a tube. Traditionally, the tapes in the neighbouring layers are wound following an alternating sense of helicity. Then, the tape edges are raised due to the Poisson effect, causing local surface irregularity and pressing into subsequent layers. We have found that this effect is less deteriorating in the case of coinciding lay angles because then the tape edges create imprints that are parallel to the tape length. Here, we present the results of investigating the AC loss performance of this innovative arrangement and its comparison with the traditional architecture. Both verification possibilities—experimental testing of small laboratory models and numerical modelling— were used for this purpose.